Penetration resistance and ballistic-impact behavior of Ti/TiAl3 metal/intermetallic laminated composites (MILCs): A computational investigation - Jennifer S. Snipes; S. Ramaswami; Mica Grujicic (AIMS materials science, 2016)
A comprehensive computational engineering analysis is carried out in order to assess suitability of the Ti/TiAl3 metal/intermetallic laminated composites (MILCs) for use in both structural and add-on armor applications. This class of composite materials consists of alternating sub-millimeter thick layers of Ti (the ductile and tough constituent) and TiAl3 (the stiff and hard constituent). In recent years, this class of materials has been investigated for potential use in light-armor applications as a replacement for the traditional metallic or polymer-matrix composite materials. Within the computational analysis, an account is given to differing functional requirements for candidate materials when used in structural and add-on ballistic armor. The analysis employed is of a transient, nonlinear-dynamics, finite-element character, and the problem investigated involves normal impact (i.e. under zero obliquity angle) of a Ti/TiAl3 MILC target plate, over a range of incident velocities, by a fragment simulating projectile (FSP). This type of analysis can provide more direct information regarding the ballistic limit of the subject armor material, as well as help with the identification of the nature and the efficacy of various FSP material-deformation/erosion and kinetic-energy absorption/dissipation phenomena and processes. The results obtained clearly revealed that Ti/TiAl3 MILCs are more suitable for use in add-on ballistic, than in structural armor applications.